He Has Gone to a Better Place, but She Has Not: Health Status of Hindu Widows in India. Issue 5 (4th May 2021) - Agrawal, Ayush; Lalji, Chitwan; Pakrashi, Debayan
Abstract: Using detailed individual and household-level data from the first two rounds of the India Human Development Survey (IHDS) conducted in 2004–05 and 2011–12, this paper estimates the health gap that exists between married and widowed women from Hindu households. We use the most commonly used anthropometric indicators of nutritional status in adults – body mass index and incidence of underweight – to estimate and decompose the gap in health outcomes that exists between these two groups of women. The overall results presented in this paper suggest that widows from Hindu households have significantly lower body mass index and higher incidence of underweight compared to their married counterparts and also experience high levels of discrimination. Access to various government welfare schemes and increased autonomy, however, is found to offset the detrimental health effects of widowhood to a large extent.